The perspective of the development of social networks in the context of local pro-family policy - Ozorowski, ks. Mieczysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The aim of the article was to present the perspective of the development of social networks aimed at supporting the family as an institution in its integral functioning. At the beginning, the concept of a social network was explained. Then, the place of social networks in the framework of local policy was presented. Finally, the basic principles of the operation of social networks were discussed. People have long been trying to create social networks to pursue their interests. They become especially active in the face of various difficulties such as illness, accident, natural disaster. This article was about the organization of institutional networks working to help the family.